The Impact of Using Combine Harvester on Economic Factors of Rice Farmers in Gowa Regency - Rudy Immanuel Pundising; Laode Asrul; Mahyuddin (Publisher Cv. Inara, 2021)
Efforts from a development process cannot be separated from the existence of effective agricultural information and technology as well as accurate information in the hope that there will be changes in the behaviour and abilities of farmers in farming activities and increased production to realize the goals of a development process, namely rice self-sufficiency. Gowa Regency is a district whose population is mostly engaged in agriculture and areas that do not escape the government's attention, especially in the agricultural sector. In applying new technology, of course, there must be the roles of certain parties in the application of technology, both from the government, extension agents and farmers (target/community). The data needed in this study are primary data and secondary data. Primary data is data obtained directly from the field through direct interviews with sample farmers who are guided by prepared questionnaires. The data obtained are primary and secondary data processed by quantitative methods. In this study, the analysis used is the different test for two different samples (t-test) and the Structural Equation Model (SEM) analysis model. Combine harvester affects the socio-economic income of lowland rice farmers in Gowa Regency with the presence of agricultural machine tools combine harvester, so rice farmers are more benefited from a time-efficient point of view and the need for labour was minimal and income also increased by about 15% from conventional harvesting. There is a need for socialization of the use and utilization of agricultural so that farmers are more interested in using agricultural machine tools in the field.